IMPROVING STUDENTS' SPEAKING SKILLS USING SPEAKING BINGO GAME - Nur laila Khoirina; Setia Rini (Universitas PGRI Semarang, 2021)
This research aimed to find out the improvement of students’ ability by using speaking bingo game in speaking for the seventh grade students of SMP Muhammadiyah Salatiga. The classroom action research adopted two cycles consisted of steps based on Kemmis and Taggart; planning, acting, observing, and reflecting. In each cycle comprised of pre-test, treatment, and post-test. The information gathered were subjective and quantitative information. The subjective information were acquired through perception, and documentation. Tests are utilized to gather the quantitative information. The understudies improve their talking abilities after instructed by talking bingo game and the mean of post-test is higher than the mean of the pre-test. The mean of pre-test are 57.0, while post-test is 61.8. In the cycle II, the mean of post-test is higher than the mean of the pre-test. The mean pre-test are 65.6, while post-test is 72.0. There is huge improvement for understudies talking abilities utilizing talking bingo game. The consequence of T-test in cycle I is 4.485 and cycle II is 6.025. In addition, the t-test in the cycle II is greater than the t-trial of the cycle I. From the outcome, the finish of the examination on utilizing talking bingo game can improve the 7th grade understudies' capacity in talking at SMP Muhammadiyah Salatiga fundamentally.Key Words: Speaking Bingo Game and Speaking Ability.